PENGARUH PAJAK DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN ACEH UTARA (Fokus Ekonomi, 2010)
The objectives this study is to test effect of taxes and local fee upon local revenue. This study using secondary data form taxes, local fee and local revenue obtaining from the office of management financial and wealth assets in the North Aceh, 1990-2007. The results researh found that taxes and local fee significant effect to local revenue. However, the research also found that partial only tax significant effect on the local revenue. These results indicate that the local government of North Aceh had not done a good collection of local fee. So, North Aceh government is expected to forward more vigorously to seek new sources of user charges to raise local revenue.